2019
DOI: 10.1111/cpr.12703
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐34 mediated by hepatitis B virus X protein via CCAAT/enhancer‐binding protein α contributes to the proliferation and migration of hepatoma cells

Abstract: Objectives Interleukin‐34 (IL‐34) is associated with hepatitis B virus (HBV) infection and hepatocellular carcinoma (HCC). However, the role and associated mechanisms of IL‐34 in HBV‐related HCC remain unclear. In this study, the expression, biological function and associated mechanisms of IL‐34 in HBV‐related HCC cells were investigated. Methods IL‐34 expression induced by HBV and HBV X (HBX) gene was measured in hepatoma cells. The role of CCAAT/enhancer‐binding protein α (CEBP/α) in HBX‐induced IL‐34 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…HBV is also a major factor associated with the development of hepatocellular carcinoma (HCC). Expression of the HBx viral particle in HCC-infected cells induced expression of IL-34, which promoted cancer cell proliferation and migration via CSF-1R and syndecan-1 receptors in an ERK- and STAT3-dependent manner 84 .…”
Section: From Monocytes To “Non-resident” Macrophagesmentioning
confidence: 99%
“…HBV is also a major factor associated with the development of hepatocellular carcinoma (HCC). Expression of the HBx viral particle in HCC-infected cells induced expression of IL-34, which promoted cancer cell proliferation and migration via CSF-1R and syndecan-1 receptors in an ERK- and STAT3-dependent manner 84 .…”
Section: From Monocytes To “Non-resident” Macrophagesmentioning
confidence: 99%
“…Upregulation of Bcl-xL expression causes a decrease in the apoptotic potential of HCC cells that contributes to their survival, intensified growth, and colony formation [ 44 ]. The study of Kong et al [ 45 ] on HBV-positive HCC has shown that HBV causes an increase in Bcl-xL in an IL-34-dependent manner [ 45 ].…”
Section: The Role Of Bcl-xl In Hbv Infectionmentioning
confidence: 99%
“…Besides, we executed a TF-EAGs network to investigate the possible transcription factors of these 96 EAGs. Among these transcription factors (TFs), CEBP, AP1, STAT3 have been reported to mediate oncogenic effects of other substances in HCC, indicating that these TFs might have potential research values in HCC [21][22][23]. Through the analysis of gene sequencing data and clinical prognostic information of HCC patients, a prognostic risk model was constructed by 5 hub prognosisrelated EAGs, including LGALS1, MMP1, P3H1, ITGB5, and SPP1.…”
Section: Discussionmentioning
confidence: 99%